Kinetic spectrophotometric method for the determination of some fourth generation fluoroquinolones in bulk and in pharmaceutical formulations - Akram M. El-Didamony; Mona O. Abo-Elsoad (Journal of Saudi Chemical Society)
A kinetic spectrophotometric method for accurate and sensitive determination of gemifloxacin (GMFX) and gatifloxacin (GTFX) has been described. The method is based on the reaction of the studied drugs with potassium permanganate in the presence of sodium hydroxide to form a water-soluble green product which shows maximum absorbance at 604 nm. The determination of GMFX and GTFX drugs by rate constant, fixed-concentration, and fixed time methods was feasible with the calibration equations obtained but the fixed time method had been found to be more applicable. The concentration of the selected drugs is calculated using the calibration equation for the fixed time method. The absorbance–concentration plot is linear over the range of 4–36 μg mL−1 and 4–40 μg mL−1 with correlation coefficient of 0.9998 and 0.9991, for GMFX and GTFX, respectively. The molar absorptivity, Sandell sensitivity, detection and quantification limits were also calculated. The different experimental parameters affecting the development and stability of the color were carefully studied and optimized. The intra- and inter-day RSD values indicated the ruggedness of the method. The proposed method has been successfully applied to pharmaceutical formulations of each drug. Statistical comparison of the results with a well established reported method showed excellent agreement and proved that there is no significant difference in the accuracy and precision.